Preservation of Indonesian Culture through Traditional Games Application - Elsa Regiana; Albertus Dwiyoga; FX Hendra Prasetya (SISFORMA, 2020)
In the face of technological developments that are more advanced, it takes action to preserve the culture. Preservation of Indonesian culture can be done through the media game. Although the game play still has a bad image in the eyes of the parents, but slowly this negative stigma may be reduced if the digital game can be packaged properly as an example as a means to educate children.For that traditional game application titled Ensiklo Dolanan made with the concept of educational games by presenting information and games around the traditional games are packaged in an interesting way to increase the enthusiasm of children in the effort to preserve the traditional game